Strengthening mechanism of lamellar-structured Ti–Ta alloys prepared by powder metallurgy - Chufan Wang; Qi Cai; Jinxu Liu; Xifeng Yan (Journal of Materials Research and Technology, 2022)
Titanium-tantalum alloys with lamellar microstructure were fabricated by cold isostatic pressing under 400 MPa and pressure-free sintering at 1600 °C. By such a low-cost powder metallurgy method, the Ti–Ta alloy exhibited the tensile yield strength of 1124 MPa at room temperature, which was twice that of the cast Ti–Ta alloys. The microstructure and mechanical properties were characterized in detail to elucidate the deformation behavior and the strengthening mechanism of the Ti–Ta alloys prepared by powder metallurgy. With the increasing Ta content, the width of the α laths decreased, and that of the β laths increased, leading to the precipitation of the acicular α in the β laths. Correspondingly, the yield and ultimate strength increased, while the strain to failure decreased. Lamellar structure strengthening was determined to be the dominating mechanism for the high strength of the Ti–Ta alloys prepared by powder metallurgy. After quantitatively evaluating the contributions of laths, solute atoms, prior β grain boundaries, and dislocations, a model was established to illustrate the yield strength of the Ti–Ta alloys. The calculated values agreed well with the measured strength values of the Ti–Ta alloys, indicating that this model is effective in forecasting the strength of the dual-phase Ti alloys with lamellar structure.